Now See Hear! : Art, language and translation - Wedde, Ian; Burke, Gregory (Wellington : Wellington City Art Gallery, 1990)
Art & Language ; Brown, Mary-Louise ; Rhodes, Pauline ; Tweedie, Merylyn ; Drummond, Andrew ; Reynolds, John ; Callas, Peter ; etc.
Now See Hear! : Art, language and translation, Wellington City Art Gallery, Wellington, July - October 1990
Engels
kunstcatalogus